URGENSI BUMDES SYARIAH KEMBANG SETANJUNG DALAM PEMBANGUNAN PEREKONOMIAN DESA TANJUNG MEDAN - Sahat Sihotang (Fakultas Ekonomi Universitas Pasir Pengaraian, 2023)
Efforts to improve welfare are carried out by seeking to develop original village income sources (PADes). The village's sources of income include business entities, or Village-Owned Enterprises (BUMDes). Village-Owned Enterprises aim to manage village assets well, improve village economic governance systems, and realize village community welfare in accordance with the national development goals of creating a just and prosperous society that is evenly distributed materially and spiritually based on Pancasila and the 1945 Constitution. The focus of this research is the urgency of Kembang Setanjung Sharia BUMDes in the economic development of Tanjung Medan Village. The research method used in this research is descriptive qualitative research method. Data collection techniques were through interviews with the Kembang Setanjung Syariah BUMDes manager in Tanjung Medan Village, field observations, and literature studies using journals and books related to this research. The informants for this research are the village head, the director of BUMDes Syariah Kembang Setanjung, Tanjung Medan Village. The validation technique used in this research is to use data triangulation from the data obtained through the three data collection techniques. The results of the study show that the urgency of BUMDes Syariah Kembang Setanjung in the economic development of Tanjung Medan Village as a community-based economic power will make BUMDes truly advance the village economy and ultimately drive positive national economic growth.